Influence of surface tensions of solvent/nonsolvent mixtures in membrane casting solutions on the performance of poly(2,6-dimethyl-1,4-phenylene)oxide membranes for gas separation applications - Tan, J. M. A.; Noh, S. -H.; Chowdhurry, G.; Matsuura, T.
Surface tension measurements were used to assess the viability of the membrane-casting system for poly(2,6-dimethyl-1,4-phenylene)oxide asymmetric membranes for gas separation. The data was obtained from solvent(chloroform)/nonsolvent additive solutions. The nonsolvent additive was varied consisting of linear, straight and branched alcohols. It is illustrated how surface tension data can be used to elucidate the role of nodules on the surface of the asymmetric membranes.
Keywords: SEPARATION; ASYMMETRIC MEMBRANE; SURFACE TENSION; PPO; NODULES